SISTEM PAKAR DIAGNOSA PENYAKIT HIPERTENSI MENGGUNAKAN METODE NAIVE BAYES PADA RSUD ALOE SABOE KOTA GORONTALO - Puspa, Misrawati Aprilyana (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2018)
Hipertention is desease that happen to arteries that caused the supply of oxygen and nutrition that need by the body blocked. Hipertention often call as a silent killer, because it kind of disease that very harmful but come without awareness to it’s victim. People with hipertention in average is up to 40 years old and it happened all of his after life . In common hipertention caused by heredity, unhealthy lifestyle, and trigger by the more salty consumption, alcohol and stress. Expert system could be the solution to solve the problem because this system is worked just like an expert and created by naïve bayes method with the rule and basic system that same just like the hipertantiondesease. Through this application, user can do consultation with this system just like usually people consultation with the expert to diagnostic the sign that happen to user and find the solution of what happened to themselves.